A Comparative Study of Modern Economics and Kautilya’s "Arthashastra" - Khadka, Ashok Kumar (Pashupati Pragya पशुपति प्रज्ञा, 2025)
In essence, Kautilya's "Arthashastra" is a guide for running a state. There are fifteen volumes in the Arthashastra. Of them, the first five deal with internal administration, the next eight with relations with neighboring states, and the last two with other subjects. The two primary objectives of Kautilya's Arthashastra are to maximise resources and manage them as effectively as possible. His economic theories from the fourth century B.C. are discussed in this essay along with their relevance today. The entirety of the examination shows that Kautilya's economic theories are based on certain scientific concepts. An excellent way to establish rules for state administration is through Arthashastra. His economic theories are still relevant today. Therefore, this outstanding leader and philosopher deserves a special place among the greatest thinkers in the history of economics.